Knee pain in young sports players aged 6-15 years: a cross-sectional study in Japan - Iwatsu, J.; Yabe, Y.; Sekiguchi, T.; Momma, H.; Tsuchiya, M.; Kanazawa, K.; Yoshida, S.; Sogi, Y.; Nagatomi, R.; Hagiwara, Y. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Knee is the most commonly injured part of the body in young athletes. Knee pain in several studies have been seen to be more prevalent in active adolescents compared to inactive, although common in both groups. Nevertheless, few studies with large sample size have been published reporting the difference of the prevalence of knee pain for each sport among young sports players. This study investigated the point prevalence of knee pain among young sports players aged 6-15 years old according to age, sex, and sports discipline. Furthermore, this study investigated the association between knee pain and sports discipline among young sports players.